Penerapan Teknologi Honeypot untuk Meningkatkan Keamanan Jaringan BMKG - Ruth Archana Sihombing (Journal of Computation Physics and Earth Science (JoCPES), 2022)
The quick advancement of innovation has expanded the modernity of cyber dangers, requiring strong security measures to protect basic frameworks such as those overseen by the Meteorology, Climatology, and Geophysics Office (BMKG). This think about centers on the execution of honeypot innovation as a proactive defense component to upgrade BMKG's organize security. A case think about approach was conducted at Sekolah Tinggi Teknologi Adisutjipto, recreating BMKG organize situations to analyze and assess the viability of honeypots in recognizing and moderating cyberattacks. The investigate included the plan, arrangement, and testing of a honeypot framework custom fitted to imitate BMKG's arrange structure, capturing pernicious activity and recognizing assault designs. Comes about illustrated that the honeypot successfully recognized unauthorized get to endeavors, given experiences into attacker behaviors, and decreased the hazard of information breaches by redirecting malevolent on-screen characters absent from real systems. This paper concludes that executing honeypot innovation essentially upgrades arrange security by advertising real-time checking, risk investigation, and an extra layer of assurance against cyber dangers. The discoveries give a viable system for BMKG and other basic educate in receiving honeypots as portion of their cybersecurity methodologies. Future investigate seem investigate coordination honeypots with other progressed innovations, such as machine learning, to assist move forward security defenses.